Stillbirth as risk factor for depression and anxiety in the subsequent pregnancy: cohort study - Hughes, P M (British Medical Journal, 1999)
OBJECTIVE: To assess women’s symptoms of depression and anxiety during pregnancy and the postpartum year in the pregnancy after stillbirth; to assess relevance of time since loss. DESIGN: Cohort study with four assessments: in third trimester and 6 weeks, 6 months, and 12 months after birth. SETTING: Outpatient departments of three district general hospitals; subjects’ homes. SUBJECTS: 60 women whose previous pregnancy ended in stillbirth after 18 weeks’ gestation; 60 matched controls. MAIN OUTCOME MEASURES: Depression and anxiety measured by Edinburgh postnatal depression scale, Beck depression inventory, and Spielberger state-trait anxiety scale. RESULTS: In the third trimester women whose previous pregnancy had ended in stillbirth were significantly more depressed than control women (10.8 v 8.2; P=0.004) and had greater state anxiety (39.8 v 32.8, P=0.003) The difference was accounted for by those women who conceived less than 12 months after the stillbirth, who were also more depressed at 1 year. Results in those who conceived 12 months or more after stillbirth were similar to those in their controls at all points and showed lower trait anxiety 1 year post partum. One year after the birth 8% of control women and 19% of subjects scored high for depression (P=0.39), with most of the depression among the more recently bereaved (28% v 11%; P=0.18). In the women who had experienced stillbirth, depression in the third trimester was highly predictive of depression 1 year after subsequent birth (P⩽0.0005). CONCLUSION: Vulnerability to depression and anxiety in the next pregnancy and puerperium is related to time since stillbirth, with more recently bereaved women at significantly greater risk than controls. As there are problems for mother and infant associated with high anxiety and depression during and after pregnancy, there may be advantage in waiting 12 months before the next conception.